Strategies for diverse participant recruitment to a preclinical Alzheimer's Disease prevention trial: The AHEAD study. (20th December 2022) - Molina‐Henry, Doris P.; Grill, Joshua; Sperling, Reisa A.; Aisen, Paul; Clanton, Taylor; Devins, Theresa; Dhadda, Shobha; Glover, Crystal M; Irizarry, Michael C; Johnson, Keith A.; Kirn, Dylan; Kramer, Lynn D; et al.
Abstract: Background: Improving the demographic diversity of clinical trial participants, including preclinical Alzheimer's disease (AD) trial participants, is a scientific, social, and ethical imperative. Method: The AHEAD Study is an ongoing preclinical AD trial evaluating the efficacy of lecanemab (BAN2401) in biological and cognitive disease progression in cognitively unimpaired biomarker eligible individuals ages 55‐80. The study has an overall goal of at least 15% randomizations from underrepresented populations. The AHEAD Recruitment and Retention Workgroup designed a comprehensive and collaborative recruitment plan tailored to increase diverse participation. Result: Recruitment strategies spanned central infrastructure and national initiatives, existing trial ready cohorts, enhanced site engagement, community outreach, and whenever possible, implementation of evidence‐based tactics. Central infrastructure includes a national call center, a study website with capacity for prescreening and site referral, including priority flags for underrepresented groups at the pre‐screener level; establishment of a website dedicated to Spanish speakers; and implementation of blood‐based screening across all sites and targeted communities. Site engagement approaches include disbursement of specialized funding to support local recruitment efforts tailored to diverse populations and the development of partnerships with community organizations or across sites within a region. Outreach activities, at the national, regional, and local level, include earned media and social media campaigns and award‐winning plays and videos surrounding themes of participation of diverse groups in clinical trials. Throughout, additional funding opportunities enable testing of innovative approaches and novel partnerships for recruitment of underrepresented groups at individual sites. Evaluation and additional support of these initiatives will be based on number of underrepresented participants pre‐screened, screened, and randomized in the study. Conclusion: Focused, multipronged approaches and sustainable partnerships with demographically diverse communities are required to promote the participation of underrepresented groups into preclinical AD trials like AHEAD. Our initiatives demonstrate the commitment to increase recruitment of underrepresented groups by supporting successful efforts centrally, at the site‐level and the participant level using a combination of traditional and modern recruitment approaches.